Effective School Research: Will It Play in the Country? - Joan L. Buttram; Robert V. Carlson (Journal of Research in Rural Education, 1983)
This article examines the potential application of the effective school research and model to rural school settings. Three strategies were used to orient rural educators to this body of research: (I) short-term awareness-raising sessions; (2) graduate level courses on the effective school research and model; and (3) actual conduct of the school assessment and improvement process in a rural school. The authors conclude that there is much relevance of effective schools research and practices to rural school settings but important adaptations must be considered to truly acquire the payoff desired.